2018
DOI: 10.1007/s10530-018-1834-9
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing routes of invasion of Obama nungara (Platyhelminthes: Tricladida) in the Iberian Peninsula

Abstract: Among other factors, globalization has promoted the spread of alien organisms, posing a great risk to Earth's biodiversity. Land planarians of the family Geoplanidae especially benefit from human-mediated transport. Many species become established in new areas, where they represent threats to the native soil fauna. Obama nungara is a species described from Brazil, but with many well-established populations in Europe. In this study, specimens from Argentina, Brazil, Portugal and Spain were morphologically and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
5
5
0
3
Order By: Relevance
“…Our analysis of available sequences, at the present time, suggests that the 'Argentina 2' population in Europe is still restricted to Spain, while the 'Argentina 1' population is widely present in most invaded European countries. Our analysis confirms published findings (Lago- Barcia et al, 2019), with specimens from additional countries. Our matrix includes a higher number of sequences of O. nungara (91 vs. 66).…”
Section: Populations Of O Nungara and The Invasion Of Europesupporting
confidence: 92%
See 2 more Smart Citations
“…Our analysis of available sequences, at the present time, suggests that the 'Argentina 2' population in Europe is still restricted to Spain, while the 'Argentina 1' population is widely present in most invaded European countries. Our analysis confirms published findings (Lago- Barcia et al, 2019), with specimens from additional countries. Our matrix includes a higher number of sequences of O. nungara (91 vs. 66).…”
Section: Populations Of O Nungara and The Invasion Of Europesupporting
confidence: 92%
“…We found a total of 19 haplotypes (vs. 21) for O. nungara, including 10 haplotypes in the largest network, 'Argentina 1' compared to 11 in the corresponding 'Network 3' in the previous study. Our results therefore confirm and expand the conclusions of Lago- Barcia et al (2019). For future studies on O. nungara, COI sequences, with a large amount of data available, will certainly remain a primary choice, but more variable sequences will be useful for a finer analysis of the invasion.…”
Section: Populations Of O Nungara and The Invasion Of Europesupporting
confidence: 85%
See 1 more Smart Citation
“…Following Justine, Winsor, et al (2014), such introductions can be classified either as ‘old’, for those documented during the 19th century, or as ‘new’ ones, for those occurred during the 20th and 21st centuries. The latter group includes Obama nungara Carbayo, Álvarez‐Presas, Jones, & Riutort, 2016, which is native to southern South America, and has been recently introduced into Europe (Carbayo et al, 2016; Justine, Winsor, Gey, Gros, & Thévenot, 2020; Lago‐Barcia et al., 2015, 2019; Soors, Van Den Neucker, Halfmaerten, Neyrinck, & De Baere, 2019). O. nungara appears to be the only species of the genus Obama Carbayo et al, 2013 (to date represented by 37 species), and even of the subfamily Geoplaninae, recorded out of its native range.…”
Section: Introductionmentioning
confidence: 99%
“…Obama nungara was first recorded as an exotic land planarian in Europe in various localities of France (Justine et al 2014a) Figure 1C). Molecular data (Lago-Barcia et al 2019) showed that this species is formed by three different clades and while one of these clades is restricted to Brazil, the other ones are found in Europe. This study also identified Argentina as the country of origin of the two invasive clades found in Europe.…”
mentioning
confidence: 98%